Creating A Healthy and Quality Youth Generation by Establishing a Teenagers Posyandu - Ramadhan, Adihtya; Firmansyah, Dicky; Rohimah, Hanny; Fatinah, Hasna; Aulia, Neza; Karenina, Puteri; Syaputra, Rangga; Fatmawati, Rosia; Handayani, Hani (AbdimasMu UMTAS, 2024)
Adolescence is a period of transition from childhood to adulthood. During this period, adolescents experience many challenges both from themselves (biopsychosocial factors) and the environment (environmental factors). According to WHO, adolescence occurs in the age range of 12-24 years. Meanwhile, according to the Regulation of the Minister of Health of the Republic of Indonesia Number 25 of 2014, the meaning of adolescents is a population aged 10-19 years. Adolescence is a transitional period of human mental, physical and reproductive development that can have an impact on general health status. In adolescence, various changes occur in children as a form of puberty such as weight, height and so on. The development of information and technology can influence healthy adolescent behavior including risky behavior. Problems that usually occur in adolescents include juvenile delinquency, difficulty concentrating, lack of confidence, drug and narcotic abuse, to smoking. The purpose of this community service is to spur community development by growing its own motivational power, as well as being an agent of change and preparing development cadres and forming a youth posyandu in Jayagiri Village, Ciamis Regency. Youth Posyandu is here to help teenagers face their complex problems. The problem faced is that the youth posyandu cadres have not yet been formed and there has been no previous training so that this youth posyandu is a new thing in Jayagiri Village. The implementation method to solve this problem is to form a youth posyandu by providing training to youth posyandu members on the procedures for implementing a youth posyandu. The results and outputs produced are the formation of youth posyandu cadres by implementing a 5 table cadre training system for registration, implementation of height weighing examinations, recording, services and counseling and counseling.